The connections of the insular VEN area in great apes: A histologically-guided ex vivo diffusion tractography study. (December 2020) - Cabeen, Ryan P.; Glass, Laura; Erwin, Joseph M.; Hof, Patrick R.; Toga, Arthur W.; Allman, John M.
Highlights: The connections of the VEN area in anterior insula were mapped with ex-vivo diffusion tractography in apes. The insular VEN area is connected to highest levels of visual and polysensory processing in the temporal lobe. The insular VEN area is connected with several sensory systems and also systems mediating appetite, reward, aversion and motivation. Circuitry of the insular VEN area with frontopolar areas may influence the motivation to explore and make choices. These choices may relate to foraging and socialization, and work in step with introspective states and their resulting strategies and insights. Abstract: We mapped the connections of the insular von Economo neuron (VEN) area in ex vivo brains of a bonobo, an orangutan and two gorillas with high angular resolution diffusion MRI imaging acquired in 36 h imaging sessions for each brain. The apes died of natural causes without neurological disorders. The localization of the insular VEN area was based on cresyl violet-stained histological sections from each brain that were coregistered with structural and diffusion images from the same individuals. Diffusion MRI tractography showed that the insular VEN area is connected with olfactory, gustatory, visual and other sensory systems, as well as systems for the mediation of appetite, reward, aversion and motivation. The insular VEN area in apes is most strongly connected with frontopolar cortex, which could support their capacity to choose voluntarily among alternative courses of action particularly in exploring for food resources. The frontopolar cortex may also support their capacity to take note of potential resources for harvesting in the future (prospective memory). All of these faculties may support insight and volitional choice when contemplating courses of action as opposed to rule-based decision-making.